Does micronutrient supplementation improve outcomes in adult gastrointestinal surgery patients? A systematic review - Salman, Daoud; Smith, Trevor; Calder, Philip C. (Frontiers in Nutrition, 2025)
IntroductionGastrointestinal surgery can result in short-term (in hospital) complications such as infections, post-operative ileus and poor wound healing and longer-term (post-discharge) complications such as intestinal failure, malnutrition and loss of bone mass. These complications can severely impact the patient and increase healthcare costs. Impaired immunity, excessive inflammation and oxidative stress can contribute to postoperative complications and poor outcome. Many micronutrients support immunity and help to control inflammation and oxidative stress. Therefore, providing micronutrients could mitigate poor outcome from surgery. The aim of this systematic review was to collate findings from randomized controlled trials (RCTs) of micronutrients provided to adult patients undergoing, or who had undergone, gastrointestinal surgery.MethodsSearches were conducted in Medline and CINHAL; only literature from 2014 onwards was searched.ResultsA total of 12 articles reporting data from 11 RCTs were included. These trials studied vitamin D alone (administered orally) or combinations of different micronutrients (administered orally, intravenously or in wound dressings). Six trials started the intervention following discharge from hospital. Six trials had a low risk of bias overall, while five had some concerns. Two trials found that vitamin D decreased the loss of bone density in those who had undergone bariatric surgery, but two other trials did not find this; vitamin D dose may be important in determining its effect. One trial found that vitamin D improved quality of life in those who had surgery and another found that vitamin D improved survival time and prevented relapse in some patients who had surgery for gastrointestinal cancer. Another trial found that vitamin D helped support the immune response following surgery; this could lead to fewer infections, although that outcome was not reported. Intravenous multivitamins shortened hospital stay and decreased oxidative stress in the immediate postoperative period in one trial. Using vitamin E and silicone in wound dressings decreased surgical site infection, postoperative pain, inflammation and hospital stay in one trial.DiscussionAlthough some micronutrients may reduce risk of short- and long-term complications of surgery, insufficient trials have been conducted to make strong conclusions. Further research, especially with interventions in the perioperative period and looking at in-hospital outcomes, is needed.